Identifikasi Beberapa Spesies Serangga pada Kedelai (Glycine max (L). Merr) Impor Asal Amerika Serikat - Ginting, Tri Yaninta; Mutia Z.A., Hanifah; Hutabarat, Rismawati (UNIVERSITAS LABUHANBATU, 2023)
Soybeans are one of the commodities imported by Indonesia from the United States. The imported soybeans have the potential to carry plant pests, including insects. This study aims to identify plant pests carried by soybeans, particularly insects, originating from the United States. The study was conducted at the Agricultural Quarantine Laboratory of the Belawan Agriculture Center on Sampul Street, Medan. The research was carried out from June to December 2022. The materials used in this study were soybean seeds imported from the United States, obtained from field sampling or from the integrated physical examination room of PT. GrahaSegara Integrated Physical Examination Place (TPFT). The materials used included 70 percent alcohol, lactophenol blue, blotting paper, aquades, chloroacetic acid, tissue, and glass cloth. The equipment used in this study included a compound microscope, stereo microscope, oven, laminar air flow, magnifying glass, plastic bag, bottle, plastic tray, scale, glass beaker, petri dish, brush, forceps, glass slide, and cover glass. The identification method used in this study was direct examination. The diversity of plant pests carried by soybeans was analyzed descriptively based on macroscopic and microscopic characteristics. The direct identification of insects resulted in four species: Rhizopertha dominica, Sitophilus oryzae, Callosobruchus chinensis, and Tribolium castaneum.Â Keywords: Soybean seeds, import, insects, direct examination.